O educacional no discurso político: história e memória do movimento estudantil da UFPB (1964-1969) - Ribeiro , Luís Augusto de Mendonça (2017)
The present study aimed to investigate, historically, the educational debate in the political discourse of UFPB students, from the stories and memories of the period of repression and military authoritarianism, referring to the time frame of 1964-1969, a context of ascension and consolidation of that scheme in the country. The present research revealed the students' aspirations, the desired education model and the paths pointed out by the aforementioned movement so that their demands could be concretised in practical terms, as well as their motivations, which was necessarily due to the appreciation of the historical context In which they were inserted, for that reason, the theoretical-methodological guidelines of the New Cultural History were used and emphasizes the visibility of the student protagonism of Paraíba in resistance to the coup that was installed from April of 1964, highlighting the struggles and educational demands in the mobilization agenda of the time. In this way, the research contributed to the understanding and unveiling of student interventions and struggles around education in the national project.